Scatter Search algorithm for Protein Structure Prediction. (24th September 2009) - Mansour, Nashat; Kehyayan, Christine; Khachfe, Hassan
In this paper, we present a Scatter Search (SS) algorithm for predicting 3D structures of proteins based on torsion angles representation. Given the protein's sequence of Amino Acids (AAs), our algorithm produces a 3D structure that aims to minimise the energy function associated with the structure. SS is an evolutionary approach that is based on a population of candidate solutions. These candidates undergo evolutionary operations that combine search intensification and diversification over a number of iterations. We evaluate our algorithm on three proteins taken from a Protein Data Bank (PDB). The results show that our algorithm is able to produce 3D structures with good sub-optimal energy values. Also, the Root Mean Square Deviations (RMSD) of these structures from the reference proteins are promising within limits imposed by the assumptions made.